Clinical Validation of a New Tinnitus Assessment Technology - Hébert, Sylvie; Fournier, Philippe (Frontiers in Neurology, 2017)
Current clinical assessment of tinnitus relies mainly on self-report. Psychoacoustic assessment of tinnitus pitch and loudness are recommended but methods yield variable results. Herein we investigated the proposition that a previously validated fixed laboratory-based method (Touchscreen) and a newly developed clinically-relevant portable prototype (Stand-alone) yield comparable results in the assessment of psychoacoustic tinnitus pitch and loudness. Participants with tinnitus (N=15, 7 with normal hearing and 8 with hearing loss) and participants simulating tinnitus (Simulators, N=15) were instructed to rate the likeness of pure tones (250 – 16 kHz) to their tinnitus pitch and match their loudness using both methods presented in a counterbalanced order. Results indicate that simulators rated their “tinnitus” at lower frequencies and at louder at louder levels (~ 10 dB) compared to tinnitus participants. Tinnitus subgroups (with vs. without hearing loss) differed in their predominant tinnitus pitch (i.e., lower in the tinnitus with hearing loss subgroups) but not in their loudness matching in dB SL. Loudness at the predominant pitch was identified as a factor yielding significant sensitivity and specificity in discriminating between the two groups of participants. Importantly, despite differences in the devices’ physical presentations, likeness and loudness ratings were globally consistent between the two methods and, moreover, highly reproducible from one method to the other in both groups. All in all, both methods yielded robust tinnitus data in less than 12 minutes, with the Stand-alone having the advantage of not being dependent of learning effects, being user-friendly, and being adapted to the audiogram of each patient to further reduce testing time.